Letter (copy) - Citrine, Walter, 1887-1983
025a-0031-001 INTERNATIONAL. WMC/AC/NS/124. July 18th 1940 Mr. J. Marchbank, National Union of Railwaymen, Unity House, Euston Road, LONDON N.W.1. Dear Mr Marchbank, I am very glad to learn from your letter of the 17th instant that your Executive Committee has approved a further grant of £500 to aid the Spanish seamen who have been in our care for the past 15 months. Please convey to your Committee the Council's grateful acknowledgment of their continued solidarity with refugees from Fascism. Yours sincerely, General Secretary. 292/946/25a/31